2010
DOI: 10.1073/pnas.1006615107
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like kinase 1 phosphorylation of p150 Glued facilitates nuclear envelope breakdown during prophase

Abstract: Nuclear envelope breakdown (NEBD) is an essential step during the G2/M transition in higher eukaryotic cells. Increasing evidence supports the notion that both microtubules and microtubuleassociated motor proteins are critical regulators of NEBD. Although it has been described that p150 Glued , the major component of the dynein/dynactin complex, localizes in the nuclear envelope during prophase, the exact role of p150 Glued and its regulation during NEBD are largely elusive. Polo-like kinase 1 (Plk1), the best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 16 publications
1
52
0
1
Order By: Relevance
“…Such a cooperative phosphorylation by Aur-A and Plk1 has not previously been reported. Kif2a, Bora, and p150 glued are also phosphorylated by Aur-A and Plk1; however, cooperative phosphorylation has not been shown (41)(42)(43)(44). Therefore, this study presents a novel regulatory mechanism involving the action of Aur-A and Plk1 upon their common substrate, FADD.…”
Section: Discussionmentioning
confidence: 97%
“…Such a cooperative phosphorylation by Aur-A and Plk1 has not previously been reported. Kif2a, Bora, and p150 glued are also phosphorylated by Aur-A and Plk1; however, cooperative phosphorylation has not been shown (41)(42)(43)(44). Therefore, this study presents a novel regulatory mechanism involving the action of Aur-A and Plk1 upon their common substrate, FADD.…”
Section: Discussionmentioning
confidence: 97%
“…Glued (38), two microtubule plus-end binding proteins, enhances microtubule dynamics, consequently contributing to taxel resistance (39). Fourth, Plk1 phosphorylation of the PTEN tumor suppressor causes its inactivation and, thus, activation of the phosphatidylinositol 3-kinase (PI3K)-AKT-mTOR pathway, a major driving force for PCa progression (40).…”
Section: Discussionmentioning
confidence: 99%
“…12 For example, we previously showed that Plk1 phosphorylation of Orc2 and Hbo1, 2 members of DNA replication machinery, promotes DNA replication under stressful conditions, 32,33 eventually contributing to acquisition of resistance to drugs that inhibit DNA replication, such as gemcitabine. 34 We also showed that Plk1 phosphorylation of CLIP-170 and p150 Glued , 2 microtubule plus-end binding proteins, enhances tubulin dynamics, 35,36 thus contributing to development of resistance to taxol. 37 In addition, Plk1 elevation causes activation of androgen de novo biosynthesis pathway, eventually resulting in resistance to androgen receptor inhibitors, such as enzalutamide and abiraterone, 2 major drugs used for patients with castration-resistant prostate cancer.…”
Section: Discussionmentioning
confidence: 99%